Use of String of Pearls Locking Plate System, Intramedullary Pin and Lag Screws for the Treatment of an Intra-Articular Olecranon Fracture in a Lamb - Walmsley, Darby W.; Shaw, Tania; Kudnig, Simon T. (VCOT Open, 2019)
Objectives The aim of this study was to describe a case of an intra-articular olecranon fracture in a lamb repaired using a String of Pearls locking plate system, intramedullary pin and lag screws.Materials and Methods A 6-month-old, 20 kg, purebred male Merino lamb was referred for evaluation of a non-weight bearing lameness of the left thoracic limb of unknown duration. Orthogonal radiographic assessment of the left elbow revealed a complete, closed, long sagittal oblique, minimally displaced fracture of the olecranon involving the ulnar shaft at the level of the radial physis, extending proximally through the distal semilunar notch to the mid-body of the olecranon. The fracture was repaired using a String of Pearls locking plate system spanning both the proximal radius and olecranon, an intramedullary pin in the ulna and lag screws across the fracture line.Results Orthogonal radiographic assessment of the left elbow at 8 weeks postoperatively revealed implant quiescence with radiographic union of the fracture site. Long-term telephone follow-up at 3 and 6 months postoperatively found the patient was no longer restricted in activity, with free access to the field, and was not displaying an overt lameness.Clinical Significance The authors describe a novel method to treat an intra-articular in a lamb olecranon fracture in a lamb using a String of Pearls locking plate system, intramedullary pin and lag screws.
Keywords: olecranon fracture; sheep; String of Pearls; fracture; tension band wire